Diphtheria outbreak in Lao People's Democratic Republic, 2012–2013. Issue 36 (5th August 2016) - Sein, Carolyn; Tiwari, Tejpratap; Macneil, Adam; Wannemuehler, Kathleen; Soulaphy, Chanthavy; Souliphone, Phouthone; Reyburn, Rita; Ramirez Gonzalez, Alejandro; Watkins, Margaret; Goodson, James L.
Highlights: The diphtheria outbreak occurred in 17 provinces; Houaphan had the highest case burden. The outbreak involved children up to 15 years with 19% case fatality rate. Suboptimal DTP3 vaccination coverage likely resulted in the outbreak. Completion of 3 DTP immunization campaign rounds was recommended targeting 0–14 year olds. Abstract: Background: Diphtheria is a vaccine-preventable disease. When vaccination coverage and population immunity are low, outbreaks can occur. We investigated a diphtheria outbreak in Lao People's Democratic Republic that occurred during 2012–2013 and highlighted challenges in immunization services delivery to children in the country. Methods: We reviewed diphtheria surveillance data from April 1, 2012–May 31, 2013. A diphtheria case was defined as a respiratory illness consisting of pharyngitis, tonsillitis, or laryngitis, and an adherent tonsillar or nasopharyngeal pseudomembrane. To identify potential risk factors for diphtheria, we conducted a retrospective case-control study with two aged-matched neighborhood controls per case-patient in Houaphan Province, using bivariate analysis to calculate matched odds ratio (mOR) with 95% confidence intervals (CI). Reasons for non-vaccination among unvaccinated persons were assessed. Results: Sixty-two clinical cases of diphtheria and 12 diphtheria-related deaths were reported in seven of 17 provinces. Among case-patients, 43 (69%) were <15 years old, five (8%) reported receiving three DTP doses (DTP3), 21 (34%) had received no DTP doses, and 35 (56%) had unknown vaccination status. For the case-control study, 42 of 52 diphtheria case-patients from Houaphan province and 79 matched-controls were enrolled. Five (12%) case-patients and 20 (25%) controls had received DTP3 (mOR = 0.4, CI = 0.1–1.7). No diphtheria toxoid-containing vaccine was received by 20 (48%) case-patients and 38 (46%) controls. Among case-patients and controls with no DTP dose, 43% of case-patients and 40% of controls lacked access to routine immunization services. Conclusion: Suboptimal DTP3 coverage likely caused the outbreak. To prevent continued outbreaks, access to routine immunization services should be strengthened, outreach visits need to be increased, and missed opportunities need to be minimized. In the short term, to rapidly increase population immunity, three rounds of DTP immunization campaign should be completed, targeting children aged 0–14 years in affected provinces.